Study on micro-mechanism of the affordable housing community in urban renewal the case of Zunyi city, Guizhou province - He, Qingyan; Yang, Jianzhu; Gong, Lei (Frontiers in Environmental Science, 2023)
Affordable housing in China refers to housing with social security for low and middle income people under the unified planning and coordination of the government. In the process of urbanization, the construction of affordable housing and commercial housing should be developed in parallel, but under the role of the real estate market economy, the development of the two is unbalanced, resulting in a disparity in quantity, a large gap in quality, unreasonable management, and even residential segregation.The construction of China's affordable housing community is a huge and complex systemic project. This study focuses on a series of problems in the relationship between supply and demand of affordable housing based only on the development context of urban renewal at this stage.Based on existing literature and official data, combined with field visits and research, this study uses Vensim PLE software to build a system model for converting various types of stock into affordable housing, and to investigate the effect of various policies on solving the problem of supply and demand of it. The research results show that (1) the policies stimulate the increase of urban population and help promote the supply cycle of affordable housing; (2) under the stimulation of the supply policy of converting stock housing into affordable housing, social investment will improve by 33%-64% and the gap of affordable housing will decrease by 29%-58%; (3) under the stimulation of the policy of optimizing the management of affordable housing, the coverage rate of affordable population will improve by 3%-5% and the middle and low income households' per capita housing floor area will increase by 9%-18% l; (4) under the comprehensive influence of the combined policies, the urban population will grow healthily, the per capita income and per capita housing floor area of low- and middle-income people will be improved, the stock of housing will be reduced, the number of affordable housing will increase, the affordable housing gap will be reduced, and the affordable housing community will be developed sustainably and healthily. The research results and recommendations will provide references for the government to enact or update the policies on affordable housing.